Not the Same Me: A Novella Exploring Self-acceptance from Experiencing Acquired Physical Disability - Yunita Anggreni Suryani (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This creative work aspires to discuss the impact of acquiring a physical disability on self-acceptance in our society. As a result of the changing in the physical body, this thesis highlights the drastic shift in attitude from positive to negative self-values to the process of regaining autonomy over one’s life from ableism. These goals will be made into a story in a psychological realism novella supported by Michael Neenan's book, Developing Resilience, which explains resilience theory. Thomas is an acquired disabled man who struggles with his current life due to the pessimistic view and discrimination that control him. Seeing adversity with a negative mindset causes more severity to him and his family, together with self-rejection, which prevents the development of resilience. As his journey goes on, Thomas will have a chance to develop resilience by learning to accept his disability and helping him recover his self-value